KEBEBASAN BERTINDAK ADMINISTRASI NEGARA DALAM NEGARA HUKUM MODERN - I Dewa Ayu Widyani (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Abstract In a modern law state, freedom of the state administration or government to act that is not creating abuse of power, it therefore should be limited. Unagainst the existing law system, enacted in urgent situation for public purposes and implemented in proper government ethical basis. Keywords: modern law state; administration; government, abuse of power.